Smoking in movies and smoking initiation in adolescents: systematic review and meta-analysis - Leonardi-Bee, Jo; Nderi, Maryanne; Britton, John (Wiley, 2016)
Background and aims: Preventing young people from initiating smoking is a vital public health objective. There is strong evidence that exposure to smoking imagery in movies is associated with an increased risk of smoking uptake. However, the estimate of the magnitude of effect is not clear since previous reviews have synthesised estimates of cross-sectional and longitudinal associations. Therefore, we have performed a systematic review to quantify cross-sectional and longitudinal associations between exposure to smoking in movies and initiating smoking in adolescents.